Fuzzy Right (Left) Ideals in Hypergroupoids and Fuzzy Bi-ideals in Hypersemigroups - Kehayopulu, Niovi (Armenian Journal of Mathematics, 2018)
Most of the results on semigroups or ordered semigroups can be transferred to hypersemigroups or to ordered hypersemigroups, respectively. The same, if we replace the word "semigroup" by "groupoid", "hypersemigroup" by "hypergroupoid". We show the way we pass from fuzzy ordered semigroups to fuzzy hypersemigroups.